State Trust Lands in the West, Updated Edition : Fiduciary Duty in a Changing Landscape. - Culp, Peter W. (Policy Focus Reports., 2015)
This comprehensive report offers state trust land managers the latest strategies andtools for asset management, residential and commercial development, conservation use, and collaborative planning. Land managers will learn how to fulfill their trust responsibilitieswhile producing larger revenues for trust beneficiaries, accommodating publicinterests, and more.